1976
DOI: 10.1073/pnas.73.2.520
|View full text |Cite
|
Sign up to set email alerts
|

Interferon: purification and initial characterization from human diploid cells.

Abstract: Interferon produced by human diploid fibroblast cells in culture has been purified approximately 5000-fold. The purified interferon, when analyzed by electrophoresis on polyacrylamide gel containing sodium dodecyl sulfate, contains only one polypeptide component of 20,000 molecular weight. The interferon activity comigrates with this polypeptide, indicating identity of the activity and the polypeptide. Oxidation of this polypeptide with periodic acid and subsequent staining with Fuchsin base indicates that it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1

Year Published

1981
1981
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(37 citation statements)
references
References 22 publications
4
32
1
Order By: Relevance
“…6). The Mr of the tro-IFN, however, differed from the 20K value reported by others (Knight & Fahey, 1980;Knight, 1976;Tan et al, 1979) for IFN-fl induced in other human diploid cells but it was the same of the value obtained by Otto et al (1980) for IFN-fl induced in the FS-4 strain of human foreskin fibroblast cells by poly(rI).poly(rC). Other workers (Reynolds & Pitha, 1975;Heine et al 1981;Duc-Goiran et al, 1983) which may have resulted in the differences in their secondary structures.…”
Section: Short Communicationcontrasting
confidence: 52%
See 1 more Smart Citation
“…6). The Mr of the tro-IFN, however, differed from the 20K value reported by others (Knight & Fahey, 1980;Knight, 1976;Tan et al, 1979) for IFN-fl induced in other human diploid cells but it was the same of the value obtained by Otto et al (1980) for IFN-fl induced in the FS-4 strain of human foreskin fibroblast cells by poly(rI).poly(rC). Other workers (Reynolds & Pitha, 1975;Heine et al 1981;Duc-Goiran et al, 1983) which may have resulted in the differences in their secondary structures.…”
Section: Short Communicationcontrasting
confidence: 52%
“…We have explored the use of Blue Sepharose affinity chromatography and RP-HPLC on Separon SGX C-18 to isolate a homogeneous tro-IFN of high quality suitable for structural analysis, monoclonal antibody production and biochemical and clinical studies. The purification method described here has several advantages over a number already reported (Knight, 1976;Rubinstein et al, 1978;Okamura et al, 1980) for purifying human IFNs. The method is simple in that it involves only two steps, it yields a homogeneous product, it does not involve extremes of pH and therefore can be used successfully to purify a number of different IFNs (including acid-labile IFNs) with retention of biological activity, and can easily be scaled-up to meet the growing demand for large amounts of pure IFNs.…”
Section: Short Communicationmentioning
confidence: 99%
“…poly(C) to a specific activity of2 X 10 9 IU/mg of protein with an overall recovery of about 50%. Other workers (3,19,20,31) obtained values of2-l0 X 10 8 IU/mg of protein as the specific activity of pure human IFN-,8 from poly(I).poly(C)-induced diploid fibroblasts. The differences in the specific activity of pure IFN-,8 found by different workers may be due to the different methods of protein estimation and to varying degrees of inactivation during purification; further work is needed to determine precisely the "true" value of the specific activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that human interferon j3 is a glycoprotein (Knight Jr. 1976), and its production has been inhibited effectively by glycosylation inhibitors ). On the other hand, human interferon a is not glycosylated (Mogensen et al 1974 ;Nagata et al 1980), and production of human interferon a has been inhibited by higher concentration of the glycosylation inhibitors than a concentration of inhibitor for human interferon /3 (Stewart II & Stewart 1979).…”
Section: Discussionmentioning
confidence: 99%